2002
DOI: 10.1128/jvi.76.20.10524-10529.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Viral Attenuation

Abstract: The genetic trajectory leading to viral attenuation was studied in a canine parvovirus (CPV) strain grown on dog kidney cells for 115 transfers. Consensus sequences of viral populations at passages 0, 3, 30, 50, 80, and 115 were obtained from PCR products covering 86% of the genome; clones from each of the 80th and 115th passages were also sequenced, covering 69% of the genome. Sixteen changes were fixed in the 115th-passage virus sample. Levels of polymorphism were strikingly different over time, in part beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…After a period of adaptation, the virus became highly infectious for dogs, resulting in the pandemic that became evident in 1978-1979. The rapid rate at which parvoviruses accumulate mutations in vivo similar to observations made in studies on CPV-2 vaccinal virus, where mutations were found to accumulate rapidly during passage in tissue culture [3,84].…”
Section: Emergence Of Canine Parvovirus Strains and Its Distributionsupporting
confidence: 58%
See 1 more Smart Citation
“…After a period of adaptation, the virus became highly infectious for dogs, resulting in the pandemic that became evident in 1978-1979. The rapid rate at which parvoviruses accumulate mutations in vivo similar to observations made in studies on CPV-2 vaccinal virus, where mutations were found to accumulate rapidly during passage in tissue culture [3,84].…”
Section: Emergence Of Canine Parvovirus Strains and Its Distributionsupporting
confidence: 58%
“…Approximately 50% of the mass is protein, and the remainder is DNA. Because of the relatively high DNA-to-protein ratio, the buoyant density of the intact virion in cesium chloride (CsCl) is 1.39-1.42 g/cm 3 . Finally, the sedimentation coefficient of the virion in neutral sucrose gradients is 110-122 S [54,69].…”
Section: Etiologymentioning
confidence: 99%
“…The high homology between the BAAV and AAV-5 Rep proteins, along with the biochemically distinct mechanisms of replication for these two viruses vis-à-vis other mammalian AAVs, suggest that BAAV and AAV-5 might form a distinct group within the Dependovirus genus. Thus, BAAV and human AAV-5 might be the result of a cross-species transmission such as has been proposed for the evolutionary history of parvoviruses (1).…”
Section: Discussionmentioning
confidence: 99%
“…CPV2 strain Cornell-780916, which is the parental CPV2 in manufacturing several commercial live vaccines, was also obtained from ATCC (catalogue number: VR-953). This strain may have been propagated in CRFK cells during attenuation [1]; however, the detailed passage history is unknown. The stock viruses were stored at -80 ºC until use.…”
mentioning
confidence: 99%
“…Given that these canine vaccines contained the original antigenic type of canine parvovirus (CPV) type 2 in common, and that many such CPVs have been isolated and attenuated using CRFK cells [1,5], we suspected that RD-114 virus may have contaminated the seed stock virus for the production of the vaccines [15]. In this study, we collected CPVs from a diagnostic laboratory and American Type Culture Collection (ATCC), and checked for the presence of infectious RD-114 virus.…”
mentioning
confidence: 99%